Job Satisfaction Among Vocational Teachers in Malaysia - Mustapha, Ramlee (EDUCARE, 2009)
ABSTRACT:Â  The effect of globalisation on human capital development is decisive. A country that lacks the means to compete in global market is often left behind. Competitiveness is based on a countrys capacity to add value to global economic products, services and processes. A key contributor in this regard is the knowledge and skills of the workforce. The education and skills of the workforce will be the key competitive weapon for the 21st century. Thus, the purpose of this study was to explore the career satisfaction among vocational teachers in the selected technical secondary schools in Malaysia. The aspects that were studied include the job domain, the work environment and the flow of information within the organisation. A sample of 101 vocational teachers in Technical Secondary Schools in Negeri Sembilan and Melaka was selected. The questionnaire contained three sections: (1) profile of the respondents; (2) job satisfaction; and (3) open-ended questions. Descriptive statistics in the forms of frequency, percentage, mean and standard deviation were used for the data analysis. The study found that the environmental and job factors are the aspects which bestow job satisfaction to vocational teachers, while the aspect of flow of information within the organisation was rated low. Therefore, the school administrators need to improve the flow of information in the organisation especially between the administrators and vocational teachers in order to enhance job satisfaction among vocational educators.KEYWORDS: job satisfaction, vocational teachers, human resource development, and Job Descriptive Index in Malaysia.About the Author: Professor Dr. Ramlee Mustapha is the Director of the Centre for Learner Diversity, Faculty of Education UKM (National University of Malaysia) in Bangi, Selangor Darul Ehsan, Malaysia. He can be reached at: drramlee@yahoo.comHow to cite this article? Mustapha, Ramlee. (2009). âJob Satisfaction Among Vocational Teachers in Malaysiaâ in EDUCARE: International Journal for Educational Studies, Vol.1(2) February, pp.169-186. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (November 25, 2008); Revised (January 3, 2009); and Published (February 17, 2009).